Gambaran Perilaku Cyberbullying pada Siswa Sekolah Menengah Pertama - Awaluddin, Nuraeni; Buchori, Sahril; Syahril; Amirullah, Muhammad (Paedagogie, 2026)
This study aims to obtain a description of the level of cyberbullying behavior among students at one of the public junior high schools as a basis for developing guidance and counseling services in accordance with students' needs. This study employs a quantitative approach with a descriptive method. The population consisted of 99 eighth-grade students from three classes, while the research sample comprised 14 students determined through proportional random sampling based on their tendency toward high and very high categories of cyberbullying behavior. Data were collected through the distribution of a cyberbullying behavior scale adapted from Risyana (2020) based on Willard's (2007) aspects, consisting of 35 valid items with a Likert scale and a Cronbach's Alpha reliability coefficient of 0.939. Data were analyzed using descriptive statistical techniques in the form of percentages and category groupings. The results indicate that the majority of students were in the moderate category at 42%, followed by the high category at 29%, very high category at 7%, low category at 16%, and very low category at 5%. Thus, more than 78% of students fall within the moderate to very high categories. These findings indicate that students' digital interactions have not fully reflected mutual respect and responsibility, as characterized by tendencies to mock, taunt, and spread content that humiliates others through social media. The findings of this study indicate that guidance and counseling services play a strategic role in designing cyberbullying prevention programs focused on enhancing self-awareness, emotional regulation, empathy, and skills for positive interaction in digital spaces.